Alleged Violation of Article 29 of Law Number 5 of 1999 Jo. Article 5 Government Regulation Number 57 of 2010 Regarding Late Notification of Takeover (Acquisition) of Asian Trails Holding Ltd. Shares. By Travel Circle International (Mauritius) Ltd. Decision: 22/Kppu-M/2020 - Gunati, Mira; Tri Agus Haryono; Mijan; Yogi Angistya Tamara; Santoso, Edi (Formosa Journal of Sustainable Research, 2024)
Delay in notification of takeover of shares of Asian Trails Holding Ltd. (ATHL) by Travel Circle International (Mauritius) Ltd. (TCI) to the Business Competition Supervisory Commission (KPPU) triggering fines and raising concerns about business competition practices and fairness in the Asian tourism market. This article analyzes the factors that cause notification delays, their implications for the market, and the steps needed to prevent the recurrence of similar cases. The analysis results show that delays are caused by a combination of factors, including misunderstanding of regulations, transaction complexity, lack of internal understanding, and less than optimal communication with KPPU. This delay has the potential to trigger regulatory violations, competitive disruption, uncertainty and injustice, which can have a negative impact on consumers, business actors and the economy as a whole. Therefore, joint efforts are needed from relevant authorities, business actors and civil society to strengthen business competition law enforcement, increase regulatory awareness and build a transparent, accountable and fair tourism market ecosystem